Was machen Urologen in der Praxis? Ein erster „ungefilterter“ Blick auf die Versorgung - Goebell, Peter; El-Khadra, Sulafah; Horstmann, Marcus; Kollenbach, Peter; Luedecke, Gerson; Quack, Thomas; Rug, Michael; Stephan-Odenthal, Michael; Bode-Greuel, Kerstin; Zink, Saskia; Lieberkuehn, Patrick; Schulze, Matthias (Urologe, 2021)
The topic of routine medical care data and healthcare science has gained in relevance and provides an important basis for both healthcare policymakers and those providing care. Access to relevant data and the ability to analyze these is highly competitive as it yields the most compelling arguments and strong facts in any discourse on the ultimately limited resources of the entire healthcare sector. All randomized clinical trials and prospective data collections harbor the inherent similarity that they contain data within a predefined frame of data elements in order to control for any confounding factors. In addition, analyses using retrospective data collections use a predefined evaluation matrix and filter the existing data according to these established data elements. However, an unfiltered and un(pre)specified view to all data would be ideal. An approximation to this goal as part of this project could be the unfiltered collection of as much data as possible and their collection in a data pool, which then could be processed, in a constantly improving analyses algorithm. The automated self-extraction of data from the private-practice information technology (IT) system to UROscience will create a data pool which could be used to answer many different questions related to the reality of healthcare. The preliminary analyses presented here demonstrate that, on basis of the existing data, this versatile sample is available to provide insight into the treatment reality of urologic outpatient care.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Berufsverband der Deutschen Urologen (BvDU); Healthcare science; Real-world data; UROgister; UROscience